Research on Battery Balancing Strategies. Issue 1 (May 2021) - Yuanyuan, Li
Abstract: While being used as energy storage carriers, batteries usually need to form series-parallel modules to meet the requirements of system voltage and power. Due to the differences of materials, production process and temperature of each battery in the module, there will be unbalanced voltage. If it is not controlled, some batteries will be damaged due to overcharge or over discharge, resulting in the failure of the module or even accidents. This paper first analyzes the development of energy storage batteries, and studies the causes of the imbalance of the battery pack and the significance of its balance. Then several battery equalization methods and their working principles are studied, and the equalization process of a double-layer active equalization system is analyzed in detail, so as to improve the consistency of the batteries and extend their service life. Finally, the comparative analysis results of inductor-based equalization and transformer-based equalization are given.